2017
DOI: 10.1007/s00705-017-3258-8
|View full text |Cite
|
Sign up to set email alerts
|

The genetic diversity of bovine papillomaviruses (BPV) from different papillomatosis cases in dairy cows in Turkey

Abstract: Papillomaviruses (PVs) are epitheliotropic viruses that cause benign proliferative lesions in the skin (warts or papillomas) and mucous membranes of their natural hosts. In bovines specifically, 13 types of Bovine papillomaviruses (BPVs) are currently described in the literature, although the actual number may be greater than 20. BPV types are classified into four genera based on homology within the genomic regions of the L1 ORF, the most conserved sequence. This study conducted molecular typing of BPV in dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
1
19
2
Order By: Relevance
“…The virus was molecularly identified based on the amplification and sequencing of L1 gene fragments. As shown, a lower prevalence (3.6%) of BPV-1 infection was found in this study than previous studies either at the national or international level [ 18 , 19 , 45 , 46 ]. This difference might be attributed to various factors, including differences in cattle management systems, sampling locations, and sample sizes [ 10 , 47 , 48 ].…”
Section: Discussioncontrasting
confidence: 63%
“…The virus was molecularly identified based on the amplification and sequencing of L1 gene fragments. As shown, a lower prevalence (3.6%) of BPV-1 infection was found in this study than previous studies either at the national or international level [ 18 , 19 , 45 , 46 ]. This difference might be attributed to various factors, including differences in cattle management systems, sampling locations, and sample sizes [ 10 , 47 , 48 ].…”
Section: Discussioncontrasting
confidence: 63%
“…The benign skin and mucous membrane warts are mainly caused by the epitheliotropic papillomaviruses (PVs) [ 1 ], which are small, non-enveloped, double-stranded DNA viruses with circular genomes [ 2 ]. According to the conserved late (L1) gene, the most common 13 BPVs types are found in the four genera Xipapillomavirus , Deltapapillomavirus , Epsilonpapillomavirus , and Dyoxipapillomavirus [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infection to other animals might occur through milk, semen, and urine or vertically transmitted to the offspring [ 8 ]. It was reported that coinfection with different BPV types might occur in the same animal [ 1 ]. Although PVs are highly host-specific that usually do not cross species barriers, new variants could evolve if mutations accumulate within the virus genome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen types of BPV have been identified in cattle (De Villiers et al 2004). BPV type 1-11 can cause teat warts in dairy cattle (Dagalp et al 2017;Ogawa et al 2004). These types might cause teat warts as single or various combinations.…”
mentioning
confidence: 99%